Employee Performance Analysis as a Human Resource Asset in Batu City Government Inspectorate - Gunawan Tri Nugroho; Prihat Assih; Diyah Sukanti Cahyaningsih; Waluyo Djati (Jurnal Akuntansi dan Perpajakan, 2022)
This study aims to describe the variables of professional ethics , professional competence , locus of control, professional commitment , and employee performance in Inspectorate of Batu City, Analyze the influence of professional ethics, professional competence and locus of control on employee performance through professional commitment a t the Inspectorate of Batu City directly, and analyze the influence of professional ethics, professional competence and locus of control of professional commitment to the employee performance over the professional commitment at the Inspectorate of Batu City indirectly. Based on the research purposes , this study includes quantitative descriptive with the data collection technique used questionnaires. This study uses 43 employee as the samples with the data analysis technique used is Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) . The results show (1) The Professional Ethics variable affects the employee performance, (2) The Professional Competency variable doesn't affect the Employee Performance, (3) The Locus Of Control variable doesn't affect the Employee Performance, (4) Professional Ethics variable affects the Professional Commitment, (5) Professional Competency variable affects the Professional Commitment, (6) Locus Of Control variable affects the Professional Commitment, (7) Professional Commitment variable affects the Employee Performance, (8) Professional Commitment variable partially mediates the relationship betweeen profession ethics and employee performance (9) Commitment professional variable fully mediates the relationship between the professional competence and employee performance, and (10) Commitment Professional variable fully mediates the relationship between Locus Of Control on employee performance.